Assessment of nutritional status of elderly individuals: a Mini-Nutritional Assessment - Sökülmez Kaya, Pınar (Progress in Nutrition, 2015)
Aim: The study was designed and conducted in order to identify the nutrient consumption of the elderly individuals aged 65 years and over living at home or at a nursing home in Samsun City using the MNA test. Materials and Methods: A total of 182 elderly people aged 65 years and over participated in the study. 82 of them were staying at a nursing home and 100 were living at their own home. The study used a questionnaire including socio-demographic characteristics, the Mini-Nutritional Assessment (MNA), and the records of nutrient consumption. Anthropometric measurements were also taken. The data collected by interview method was analyzed using SPSS Version 13.5. The mean and ± SD were expressed as continuous variables, and the number and the percentage as categorical variables. The data was compared using Student’s t test, Crosstabs chi-square test and Fisher’s exact chi-square test. In all tests, p <0.05 was considered significant. Findings: The risk of malnutrition increases with age (p<0.05). BMI value showed a statistically significant decrease with advancing age (p<0.05). The elderly staying at a nursing home mostly suffer from hypertension (65.9%) while other health problems (56%) and osteoporosis (32%) are mostly observed in those living at their own home (p<0.05). All the elderly individuals consumed less than the recommended amount of energy, fiber, calcium, magnesium, iron (women), zinc, iodine (only those living at their own home) vitamin D, thiamine, riboflavine (excluding the men living at their own home), vitamin B6 and vitamin B12 (women). Conclusion: Reasons of the lack of energy and nutrients in the elderly should be investigated; and special diets should be planned according to daily needs of each elderly person. Preventive measures should be taken against health problems in old age.